2013
DOI: 10.5539/ies.v6n11p21
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes and Their Academic Performance in Nationhood Education

Abstract: The main goal of the nationhood education is to instill the sense of loyalty and passion into the nation. In a Malaysian context, several academic subjects at higher education such as Malaysian Studies, Ethnic Relations and National Language have been implemented in order to achieve the goal. Malaysian Study is one of the compulsory courses offered by all private universities in Malaysia that is intended to educate students with national values, patriotism and belongingness to the country. However, past empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It can be concluded that AQ is absolutely not much of an influence to the academic achievement of students. It has another factor that affected academic achievement such as attitudes towards an academic subject.Another factor was supported by a study from Mohd Mahzan et al, (2013) indicated that most students were not active in class activities, poor attendance and exhibited a lack of motivation to study the subject. Another interesting matter to be clarified in the context of this study is that AQ may tend not to be linked with cognitive elements such as academic achievement and IQ.…”
Section: Discussionmentioning
confidence: 69%
“…It can be concluded that AQ is absolutely not much of an influence to the academic achievement of students. It has another factor that affected academic achievement such as attitudes towards an academic subject.Another factor was supported by a study from Mohd Mahzan et al, (2013) indicated that most students were not active in class activities, poor attendance and exhibited a lack of motivation to study the subject. Another interesting matter to be clarified in the context of this study is that AQ may tend not to be linked with cognitive elements such as academic achievement and IQ.…”
Section: Discussionmentioning
confidence: 69%
“…Our results also matched those obtained by Dierks et al (2016), who reported that 12-to-19-year-old German students with high academic performance showed higher interest towards science than students with low academic performance, specifically towards activities that link science with intellectual tasks or practical tasks related to the environment. Several authors have argued that students with positive attitude towards science use more learning strategies than those with negative attitudes (Farooq et al, 2011;Awang et al, 2013). This implies that students with a favourable or positive attitude towards class contents or science courses are more likely to obtain better results because they are more likely to persist and are more willing to read and learn about subjects that interest them than those students with less favourable attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…From table 5 it is clear that most of the students underwent superficial or surface learning. It will not be improper to say that, there was negative attitude towards learning environment which had caused surface learning as evidenced from poor performance of students (Awang et. al.…”
Section: Findings and Discussionmentioning
confidence: 99%